Oxidative Stress Causes Masculinization of Genetically Female Medaka Without Elevating Cortisol - Mukai, Koki; Hara, Seiji; Sakima, Konosuke; Nozu, Ryo; Yazawa, Takashi; Kitano, Takeshi (Frontiers in Endocrinology, 2022)
Medaka (Oryzias latipes) is a teleost fish with an XX/XY sex determination system. Sex reversal from female-to-male (masculinization of XX fish) can be induced through cortisol elevation from exposure to environmental stress such as high temperature during sexual differentiation. However, the effects of oxidative stress, generated via metabolic reactions and biological defense mechanisms, on the sexual differentiation of medaka are unclear. Here, we investigated the effect of oxidative stress on medaka sexual differentiation using hydrogen peroxide (H2O2), which induces oxidative stress in vertebrates. H2O2 treatment from 0 to 5 days post-hatching induced masculinization of wild-type XX medaka, but not of gonadal soma-derived growth factor (gsdf) or peroxisome proliferator-activated receptor alpha-a (pparaa) knockout XX fish. Co-treatment with an oxidative stress inhibitor caused masculinization recovery but co-treatment with a cortisol synthesis inhibitor did not. H2O2 treatment significantly upregulated gsdf and pparaa expression in XX medaka. However, H2O2 did not elevate cortisol levels in medaka larvae during sexual differentiation. These results strongly indicate that oxidative stress induces masculinization of XX medaka without causing elevation of cortisol.